2007
DOI: 10.1002/jbm.b.30774
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cellular biocompatibility of two kinds of HAP with different nanocrystal morphology

Abstract: Two kinds of hydroxyapatite (HA) with different nanocrystal morphology were obtained via a simple aqueous precipitation method under different reactants molar ratios. Under Ca/P molar ratio of 1.67/1, rod-like crystal was produced, while under Ca/P molar ratio of 1.80/1, spherical crystal was produced. The spherical crystal was 40-60 nm in diameter, while the rod-like crystal was 40-55 nm in diameter and 79-100 nm in length. The influence of HA nanocrystal morphology on osteoblasts growth was assayed by MTT me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 87 publications
(158 reference statements)
4
48
0
1
Order By: Relevance
“…The semi-spherical nanophase as showed by the images of the topography by AFM has a grain size of around 30-100 nm and it is clear that the cell functionality and biocompatibility of the osteoblasts cells to ZnAl 2 O 4 films will be influenced by the semi-spheroid mor- phology of the surface features. Similar results have been reported for enhance adhesion and biological response to nanostructure materials and had indicated that grain size plays a crucial role in mediating on the cell adhesion to nanophase ceramics and also had been reported that spheroids material surface should be more beneficial to proliferation of osteoblastic cells [32][33][34][35][36] . Finally, Figure 5 shows the morphology of osteoblasts cells cultured onto ZnAl 2 O 4 films.…”
Section: Resultssupporting
confidence: 80%
“…The semi-spherical nanophase as showed by the images of the topography by AFM has a grain size of around 30-100 nm and it is clear that the cell functionality and biocompatibility of the osteoblasts cells to ZnAl 2 O 4 films will be influenced by the semi-spheroid mor- phology of the surface features. Similar results have been reported for enhance adhesion and biological response to nanostructure materials and had indicated that grain size plays a crucial role in mediating on the cell adhesion to nanophase ceramics and also had been reported that spheroids material surface should be more beneficial to proliferation of osteoblastic cells [32][33][34][35][36] . Finally, Figure 5 shows the morphology of osteoblasts cells cultured onto ZnAl 2 O 4 films.…”
Section: Resultssupporting
confidence: 80%
“…In our study, two kinds of HAP (rod-like and sphere-like) were obtained. The cell experiment showed that HAP with spherical nanocrystals showed more favorable properties than rod-like HAP for osteoblasts, which was also demonstrated by Zhao et al [32]. The explanation for the favorable effect of sphere-like nano-HAP on osteoblasts might be the well-organized surface which seems beneficial for filopodia protrusion.…”
Section: Discussionmentioning
confidence: 65%
“…A previous study compared ALP activity following NP exposure to two rod-shaped NPs of different sizes and did not find any significant difference between them [19,21]. Another study looking at an osteosarcoma-derived cell line found that cell proliferation was decreased in the presence of spherical-shaped HA NPs [21]. The group also reported a change in cell morphology, as observed via SEM, although this was not based on ultrastructural analysis of ECM proteins or intracellular ion concentration.…”
Section: Discussionmentioning
confidence: 98%
“…Perkin Elmer Imaging Suite version 4.1 was used to collect the data, between the range of 6000 -250 cm 21 , and the background signal was subtracted from sample data.…”
Section: Fourier-transformed Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation